2022
DOI: 10.1039/d2na00306f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and multi-scale properties of PuO2 nanoparticles: recent advances and open questions

Abstract: The review focuses on the recent relevant progresses observed about PuO2 nanoparticle syntheses and characterizations including the recently deciphered electronic, structural and physico-chemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 205 publications
(520 reference statements)
1
12
0
Order By: Relevance
“…It can be observed that the lattice parameter is essentially constant and independent of the method applied and of the reaction conditions ( Figure 5 ). Moreover, this is very close to the lattice parameter of bulk PuO 2 [ 31 , 32 , 33 ]. By contrast, the crystallite size is strongly affected by the method (and, hence, the temperature).…”
Section: Resultssupporting
confidence: 70%
“…It can be observed that the lattice parameter is essentially constant and independent of the method applied and of the reaction conditions ( Figure 5 ). Moreover, this is very close to the lattice parameter of bulk PuO 2 [ 31 , 32 , 33 ]. By contrast, the crystallite size is strongly affected by the method (and, hence, the temperature).…”
Section: Resultssupporting
confidence: 70%
“…2 nm PuO 2 -like NPs, much less is known about their formation mechanism. 11–14 The description of Pu oxo–hydroxo clusters, with a characteristic size situated somewhere between the ones of ionic and colloidal species of Pu, highlighted the relation between their core structures revealing some striking similarities with bulk PuO 2 . This suggested that bigger clusters could be formed from the assembly of those smaller molecular fragments.…”
mentioning
confidence: 98%
“…Actually, in the visible spectra recorded with CaMWT at pH 6, the intense band at 456 nm followed by a shoulder at 475 nm and the double band at 659 and 686 nm were similar to the features identified for these hexanuclear Pu(IV) clusters. ,, DOTA, acetate, and glycine clusters present similar shells around Pu, two oxygen shells at 2.19 to 2.29 Å (two or four oxygen atoms, respectively) and at 2.36 to 2.42 Å (four, six, or seven oxygen atoms, respectively). The two shells of Pu(IV) are identical with four Pu(IV) in the axial plane at 3.76 to 3.77 Å and one Pu(IV) in the equatorial plane at 5.31 to 5.35 Å. The clusters decorated by acetate or glycine showed the presence of a water molecule in the Pu(IV) coordination sphere. , This water increased the number of oxygen atoms in the Pu–O shell but did do not change the main characteristics of the complex, notably the Pu(IV)–Pu(IV) distance, which is always shorter than in colloidal structures. , …”
Section: Resultsmentioning
confidence: 99%
“…40 Another species, PuO 2 , can take a great diversity of forms. 34,41 Multiple structures have been determined with Pu−O bond distances from 2.20 to 2.44 Å and Pu−Pu distances between 3.79 and 3.90 Å. In particular, the PuO 2 solid reference from oxalate conversion has a Pu−Pu distance at 3.81 Å.…”
Section: ■ Introductionmentioning
confidence: 99%